The foundations of organizational legitimacy - CHAOUQY , Zineb; SADIQI , Khalid (Revue Internationale des Sciences de Gestion, 2023)
Legitimacy, a classic question in political science and sociology for centuries, has recently attracted increased interest in management science. This development stems from the realisation that companies can no longer be viewed in isolation from their environment, and that they now have to justify taking social expectations into account. This interest in legitimacy aims to build and develop this notion in the professional world of business. Clearly, legitimacy forges social and economic links within the company and between it and its environment. It is an element of the organisation and a key success factor to be considered at the strategic level. This paper reviews the literature on legitimacy in organisational theories. It defines the foundations of this notion and analyses the emergence of concepts that influence the perception of legitimacy within the organisational environment. The constructed nature of legitimacy is multiplied, given its differentiated aspects and complex natures. Legitimacy has to do with morality, logic, utility, context and the quality of individuals.